The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.amjsurg.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive blood transfusion protocol in liver resection patients reduces blood transfusions with no increase in patient morbidity

Abstract: Background Management of anemia in surgical oncology patients remains one of the key quality components in overall care and cost. Continued reports demonstrate the effects of hospital transfusion, which has been demonstrated to lead to a longer length of stay, more complications, and possibly worse overall oncologic outcomes. The hypothesis for this study was that a dedicated restrictive transfusion protocol in patients undergoing hepatectomy would lead to less overall blood transfusion with no increase in ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…40 Restrictive protocols for blood transfusion in patients undergoing elective hepatectomy have also been shown recently to decrease blood transfusions without increases in morbidity or mortality. 46 With regard to blood-saving measures for hepatectomy, several therapies and technical maneuvers have been examined. One single-institution, randomized controlled trial from Asia suggested that perioperative administration of tranexamic acid may decrease blood loss and eliminate the need for blood transfusion after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…40 Restrictive protocols for blood transfusion in patients undergoing elective hepatectomy have also been shown recently to decrease blood transfusions without increases in morbidity or mortality. 46 With regard to blood-saving measures for hepatectomy, several therapies and technical maneuvers have been examined. One single-institution, randomized controlled trial from Asia suggested that perioperative administration of tranexamic acid may decrease blood loss and eliminate the need for blood transfusion after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the revised 72-hour NSQIP-reported blood transfusion variable allows for improved data recording and outcome estimates compared to the pre-2010 variable, which only captured blood transfusions greater than 4 units. The interaction between extent of resection and blood transfusion has been proposed previously [8]. In addition, other surrogates of more extensive operation including intraoperative management, tumor size, and associated resections have been described [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Blood transfusion is associated with higher costs and increased risk of associated morbidity. Multiple recent studies have suggested worse oncologic outcomes most notably in patients with primary or metastatic malignancies leading to proposals for transfusion restrictions in patients undergoing hepatectomy [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Some limitations for their conclusion have to be mentioned: a) unbalanced group size (no transfusion in 151 patients vs. transfusion in 8 patients); b) important confounding variables are not reported e.g. preoperative haemoglobin, type of surgery (open vs. laparoscopic) and haemostatic management.The risk of allogenic red blood cell transfusion might be associated with major liver resection, preoperative anaemia and female sex [3,4]. Recently the concept of a multidisciplinary patient blood management in order to enhance efficacy and safety of perioperatively used blood products emerged in literature [5,6].…”
mentioning
confidence: 99%
“…The risk of allogenic red blood cell transfusion might be associated with major liver resection, preoperative anaemia and female sex [3,4]. Recently the concept of a multidisciplinary patient blood management in order to enhance efficacy and safety of perioperatively used blood products emerged in literature [5,6].…”
mentioning
confidence: 99%